2014
DOI: 10.1007/s00221-013-3811-y
|View full text |Cite
|
Sign up to set email alerts
|

Novelty detection is enhanced when attention is otherwise engaged: an event-related potential study

Abstract: Novel stimuli are detected and evaluated quickly, suggesting that processing them is a priority for the brain. In the present study, the effects of attention on this early visual novelty processing were investigated in two experiments using the event-related potential (ERP) technique. In the first experiment, participants performed two tasks that varied in the amount of attention available for novel stimuli. In the Visual Oddball task, participants responded to an infrequent target presented among standard and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 68 publications
4
23
0
Order By: Relevance
“…In another study on the effect of attention direction on the novelty processing, it was shown that processing of novel (unusual) events does not necessarily need attention (Schomaker & Meeter, 2014) that was consistent with the results of other studies indicating that direction of attention lacks strong effect on the processing of novelty (Chong et al, 2008; Tarbi, Sun, Holcomb, & Daffner, 2011). The results of these studies can also justify our observation with regard to no significant difference between the effect of unusual and usual distractors.…”
Section: Discussionsupporting
confidence: 77%
“…In another study on the effect of attention direction on the novelty processing, it was shown that processing of novel (unusual) events does not necessarily need attention (Schomaker & Meeter, 2014) that was consistent with the results of other studies indicating that direction of attention lacks strong effect on the processing of novelty (Chong et al, 2008; Tarbi, Sun, Holcomb, & Daffner, 2011). The results of these studies can also justify our observation with regard to no significant difference between the effect of unusual and usual distractors.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast, studies have demonstrated that the anterior N2 in response to perceptually novel stimuli often is not modulated by stimulus context or attention (Chong et al, 2008; Daffner et al, 2000; Schomaker, Roos, & Meeter, 2014; Tarbi et al, 2011), and can be enhanced when novel stimuli occur outside the focus of attention (Schomaker & Meeter, 2014). Moreover, in a study that varied whether frequent standard, rare target, or rare non-target stimuli consisted of simple geometric shapes or highly unusual figures, stimulus frequency and deviance from immediate context were found to have only limited influence over the size of the anterior N2.…”
Section: Introductionmentioning
confidence: 93%
“…With its posterior maximum, this positivity was more typical of a P3b elicited by the words (Katayama & Polich, 1998;Polich, 2007) than a P3a elicited by novel images (Squires et al, 1975). This is not surprising as words and not images were task-relevant here, and task relevance has been suggested to be an important factor in the generation of a P3a (Schomaker & Meeter, 2014b). In essence, the ERPs were elicited by the processing of the word, and only modulated in their amplitudes by the presence of the concomitant picture.…”
Section: Electrophysiological Signatures Of Novelty: N2a N2b and P3mentioning
confidence: 50%
“…It has been argued to be a response more to deviance from context than to novelty per se (Schomaker et al, 2014). Of note, it is only generated by stimuli that could in principle be task-relevant (Schomaker & Meeter, 2014b). However, it does not reflect target processing; targets usually elicit a later, larger and more posterior component called the P3b (Ferrari, Bradley, Codispoti, & Lang, 2010;Squires et al, 1975).…”
Section: Introductionmentioning
confidence: 98%